2009
DOI: 10.1002/pmic.200900146
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific inhibition of integrin αvβ3‐vitronectin association by a ser‐asp‐val sequence through an Arg‐Gly‐Asp‐binding site of the integrin

Abstract: A functional proteomic technology using protein chip and molecular simulation was used to demonstrate a novel biomolecular interaction between P11, a peptide containing the Ser-Asp-Val (SDV) sequence and integrin alpha v beta 3. P11 (HSDVHK) is a novel antagonistic peptide of integrin alpha v beta 3 screened from hexapeptide library through protein chip system. An in silico docking study and competitive protein chip assay revealed that the SDV sequence of P11 is able to create a stable inhibitory complex onto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…P11 has been shown to inhibit the integrin ␣ v ␤ 3 -vitronectin interaction in a dose-dependent manner (21). The SDV sequence of P11 is able to recognize the vitronectin-binding site (RGD-binding site) of integrin ␣ v ␤ 3 in a site-specific manner (22). To determine the antiangiogenic mechanism of P11 as an antagonist of integrin ␣ v ␤ 3 , we first examined the effect of P11 on endothelial cell proliferation.…”
Section: Antiproliferation In P11-treated Huvecs-we Identified P11mentioning
confidence: 99%
See 1 more Smart Citation
“…P11 has been shown to inhibit the integrin ␣ v ␤ 3 -vitronectin interaction in a dose-dependent manner (21). The SDV sequence of P11 is able to recognize the vitronectin-binding site (RGD-binding site) of integrin ␣ v ␤ 3 in a site-specific manner (22). To determine the antiangiogenic mechanism of P11 as an antagonist of integrin ␣ v ␤ 3 , we first examined the effect of P11 on endothelial cell proliferation.…”
Section: Antiproliferation In P11-treated Huvecs-we Identified P11mentioning
confidence: 99%
“…In our previous study, P11, a novel peptide sequence containing Ser-Asp-Val (SDV), was shown to specifically bind to integrin ␣ v ␤ 3 instead of the RGD sequence, a common binding motif of the integrin receptor (22). The SDV sequence is a type I PDZ-binding domain (S/T-X-V) that can recognize PSD-95 (63).…”
Section: Pharmacoproteomic Analysis Of P11mentioning
confidence: 99%
“…Since this size is similar to the heavy chain of the antibody, which is also tyrosine-sulfated [52], opticin was immunoprecipitated using anti-opticin antibody and eluted under non-reducing conditions, so that the tyrosine-sulfated heavy chain of the antibody would not mask the opticin isoform. The anti-opticin antibody was successful in bringing down the 55 kD monomeric opticin band as well as multiple aggregated opticin bands of sizes 55–75 kD, with the 75 kD band being the most abundant (asterisks, Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…These two residues are close to the ‘RGD’ cell attachment site on the protein, which resides between residues 64–66. The RGD sites on vitronectin have been previously shown to bind integrin receptor αvβ3 and αvβ5 [52], [65]. However, for this to occur, the ‘RGD’ site must be exposed to the surface, which can be influenced by type of surrounding residues.…”
Section: Discussionmentioning
confidence: 99%
“…Kang and co-workers used integrin microarrays to select peptides that inhibit angiogenesis. 345,346 They first used an α v β 3 microarray and a PS-SPCL to screen for peptides that interfered with the α v β 3 –vitronectin interaction. Fluorescently labeled vitronectin was mixed with the peptide library before addition to the microarray.…”
Section: Isolation Of Disease-specific or Organ-specific Peptidesmentioning
confidence: 99%